The upper limit: how low-wage work defines punishment and welfare - Bonnet, François (University of California Press, 2019)
The upper limit -- The great adjustment : punishment and welfare in postwar America -- The crime drop and the East New York renaissance -- The necessity of harsh policing -- Prisoner reentry in public housing -- Nonprofits : welfare on the cheap -- Reengineering less eligibility : the New York homeless shelter industry.